Attachment, Coping, and Suicidal Behavior in Male Prisoners. (April 2017) - Mckeown, Annette; Clarbour, Jane; Heron, Rebecca; Thomson, Nicholas D.
The present study explored the differences between adult male prisoners with and without a history of suicidal behavior on adult attachment dimensions, coping styles, and hopelessness. The role of adult attachment and coping styles as predictors of hopelessness was also explored. The sample included 206 male prisoners from two Category B prisons in the United Kingdom. The Attachment Styles Questionnaire (ASQ), Coping Styles Questionnaire (CSQ-3), and Beck Hopelessness Scale (BHS) measured attachment, coping, and hopelessness. Prisoners with a history of suicidal behavior reported significantly higher levels of attachment anxiety, attachment avoidance, and maladaptive coping strategies. Elevated levels of attachment difficulties and maladaptive coping styles were associated with heightened levels of hopelessness. Emotional coping strategies mediated the influence of attachment anxiety and attachment avoidance on hopelessness. The study highlights the potential utility of adult attachment conceptualizations and coping skills interventions with prisoners at risk of suicidal behavior.